The Efficacy and Safety of “Kyushin” in Mongolian Patients with Ischemic Heart Disease and Heart Failure - Khasag, Altaisaikhan; Byambasukh, Oyuntugs; Narmandakh, Bayarsukh; Badarch, Amarjargal; Shukhert, Tungalag; Unurjargal, Tsolmon (Central Asian Journal of Medical Sciences, 2020)
Objectives: This study aimed to investigate the efficacy and safety of Kyushin in addition to conventional drug therapy. Methods: This study included 109 (Male/Female = 44/65) subjects were assigned to two groups (Kyushin and conventional treatment vs. conventional treatment alone) based on age, gender, and initial physiologic test values. Subjects in the Kyushin group received Kyushin 30 mg orally three times daily for eight weeks. Subjective complaints, physiological examinations (ECG, echocardiography, blood pressure, pulse rate) and laboratory tests were conducted at the start of the study and after eight weeks of treatment. The pre- and post-treatment Kyushin results were compared with the conventional treatment group’s findings. Results: In the patients treated with Kyushin, significant improvements were observed in these subjective complaints, physiological examinations (ECG, echocardiography, blood pressure, pulse rate) and laboratory tests. No adverse effects were observed during this study. Conclusions: This study shows that Kyushin is not only safe, it is more effective than conventional treatment alone in patients with ischemic heart disease and heart failure.